Are plant endogenous factors like ethylene modulators of the early oxidative stress induced by mercury? - Montero-Palmero, M. Belén; Ortega-Villasante, Cristina; Escobar, Carolina; Hernández, Luis E. (Frontiers in Environmental Science, 2014)
The induction of oxidative stress is one of the quickest symptoms appearing in plants subjected to metal stress. A transcriptional analysis of the early responses of alfalfa (Medicago sativa) seedlings to mercury (Hg; 3 μM for 3, 6 and 24 h) showed that up-regulation of genes responding to ethylene were up-regulated, a phytohormone known to mediate in the cellular redox homeostasis. In this mini-review we have compared these quick responses with two other concurrent transcriptomic analysis in Barrel medic (Medicago truncatula) and barley (Hordeum vulgare) under Hg stress. Besides ethylene, ABA, and jasmonate related genes were up-regulated, all of them are endogenous factors known to intervene in oxidative stress responses. The information obtained may target future work to understand the cellular mechanisms triggered by Hg, enabling biotechnological approaches to diminish Hg-induced phytotoxicity.